2002
DOI: 10.1093/auk/119.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of a Cryptic Species and Description of a New Subspecies in The Myrmeciza Hemimelaena Complex (Thamnophilidae) of the Neotropics

Abstract: The recording in 1992 of an unknown antbird loudsong initiated a journey of discovery that led to the resolution of the conflict between John Zimmer (1932) and Melvin Carriker (1934) regarding the taxonomic standing of the population of Myrmeciza hemimelaena, a widespread southern Amazonian antbird, that occurs in lower Andean elevations in San Martín, Peru. Zimmer had described a new subspecies, M. h. castanea, from the Moyobamba Valley, but Carriker, on the basis of specimens he collected at the same elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Although the soils were not notably poor, we observed a few species associated with poor soils, Herpsilochmus gentry (Fig. 8A Whitney 2001, 2003;Isler et al, 2002a;Isler et al, 2002b;Alvarez 1998, 2005).…”
Section: Alto Mazánmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the soils were not notably poor, we observed a few species associated with poor soils, Herpsilochmus gentry (Fig. 8A Whitney 2001, 2003;Isler et al, 2002a;Isler et al, 2002b;Alvarez 1998, 2005).…”
Section: Alto Mazánmentioning
confidence: 79%
“…Geotrygon sapphirina está ampliamente distribuida en el este del Ecuador, pero no era conocida previamente de las tierras bajas del Perú al norte del río Amazonas. 2005, J. Álvarez y sus colegas, descubrieron cuatro especies de aves nuevas para la ciencia y varias otras especies que eran registros nuevos para el Perú gracias a estudios en áreas de arena blanca cercanas aIquitos(Álvarez y Whitney 2001(Álvarez y Whitney , 2003Isler et al, 2002a;Isler et al, 2002b; Whitney y Álvarez 1998 Whitney y Álvarez , 2005. De esta forma hallaron que en los suelos de arena blanca, estas especies tenían rangos mucho más amplios en la Amazonía, especialmente en la Amazonía nororiental.De las 19 especies de aves (Álvarez y Whitney 2003) asociadas con suelos pobres, especialmente en arena blanca, encontramos 11.…”
unclassified
“…The BirdLife maps, for example, have been applied to a diversity of studies addressing macroevolution, ecology and conservation of Neotropical bird communities (Buckley & Jetz, 2008;Fluck et al, 2020;Jenkins et al, 2013Jenkins et al, , 2015Melo et al, 2009;Oliveira et al, 2016). Multiple studies have shown that many named avian subspecies in the Neotropical region represent biological species (Berv et al, 2021;Cadena et al, 2020;Chesser et al, 2020;Fernandes et al, 2012;Isler et al, 1999Isler et al, , 2002Isler et al, , 2008Isler et al, , 2009Ribas et al, 2012;Silva et al, 2019;Thom & Aleixo, 2015). With the application of molecular data and vocal analyses, cryptic taxa are often revealed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Because birdsong evolves under both natural and sexual selection, it is commonly considered to have species- [ 16 , 17 ], subspecies- [ 18 ], and population-specific [ 19 , 20 ] signals resulting from morphological divergence [ 21 , 22 ], adaptation to local acoustic environments [ 23 , 24 ], or stochastic processes, such as cultural drift [ 25 , 26 ]. Many cryptic new bird species, subspecies, and taxa have been proposed and tested according to their song variations, combined with genetic and morphological traits [ 27 , 28 , 29 ], and acoustic divergences are considered essential factors in investigations of taxonomic status or for resolving phylogenetic issues in ornithology [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%